Fibrinogen and factor XIII at the intersection of coagulation, fibrinolysis and inflammation - Hoppe, Berthold (Thrombosis and Haemostasis, 2014)
Fibrinogen and factor XIII are two essential proteins that are involved directly in fibrin gel formation as the final step of a sequence of reactions triggered by a procoagulant stimulus. Haemostasis is the most obvious function of the resulting fibrin clot. Different variables affect the conversion of fibrinogen to fibrin as well as the mode of fibrin polymerisation and fibrin crosslinking, hereby, critically influencing the architecture of the resulting fibrin network and consequently determining its mechanical strength and resistance against fibrinolysis. Due to fibrinogen’s structure with a multitude of domains and binding motifs the fibrin gel allows for complex interactions with other coagulation factors, with profibrinolytic as well as antifibrinolyic proteins, with complement factors and with various cellular receptors. These interactions enable the fibrin network to control its own further state (i. e. expansion or degradation), to influence innate immunity, and to function as a scaffold for cell migration processes. During the whole process of fibrin gel formation biologically active peptides and protein fragments are released that additionally influence cellular processes via chemotaxis or by modulating cell-cell interactions. Thus, it is not surprising that fibrinogen and factor XIII in addition to their haemostatic function influence innate immunity as well as cell-mediated reactions like wound healing, response to tissue injury or inflammatory processes. The present review summarises current knowledge of fibrinogen’s and factor XIII’s function in coagulation and fibrinolysis giving special emphasis on their relation to inflammation control.
Keywords: Fibrinogen; factor XIII; coagulation; fibrinolysis; inflammation